Late Quaternary Climate Changes around the Japanese Alps, Central Japan - 公文, 富士夫; 河合, 小百合; 木越, 智彦 (Journal of Geography (Chigaku Zasshi))
This paper reviews paleoclimate data from around the Japanese Alps in the late Quaternary period. The major data sources are total organic carbon content (TOC) of lake deposits and pollen composition from various sediments covering more than several thousand years. TOC reflects air temperature through the biological productivity of lake water. Pollen composition can show paleovegetation, and can be transformed into climate parameters using a modern analog method. The paleoclimate was reconstructed as follows under assumed conditions of altitude of 600–700m and latitude of around 36°N. Subarctic conifer forests were predominant and TOC was constantly low in the late MIS 6 (160–130 ka). It was cold as in MIS 2, the last glacial maximum. Vegetation changed significantly around 130 ka, and deciduous broadleaf trees of the cool-temperate zone became dominant in MIS 5e. TOC content in MIS 5e was also high, and temperature was as high as, or slightly cooler than, in MIS 1. Vegetation in MIS 5d to 5a comprised mixed forests of conifer trees and deciduous broadleaf trees, and their ratio changed substage by substage. TOC also fluctuated in periodicities of several thousand years, suggesting frequent temperature change. Climate in MIS 5d to 5a was a little colder than in MIS 5e and warmer than in MIS 3. The subarctic conifer forest was predominant and deciduous broadleaf trees were almost absent in MIS 4. TOC was also constantly low and temperature was much lower, as in MIS 2. Deciduous broadleaf trees flourished in MIS 3, and the ratio changed frequently in short periods of several hundreds of years to thousands of years, which corresponded to the D-O cycle. Although the annual mean temperature in MIS 3 was 5.0°C on average, that of a warm interstadial was 7.2°C and that of a cold stadial was 4.4°C. The vegetation in MIS 2 was characterized by the predominance of subarctic conifer forests and by the lowest TOC content. The reconstructed annual mean temperature was constantly around 3°C. Deciduous broadleaf trees ...